Films by gentre: 775 categories,styles, trends and movements defined, with a filmography for each - Lopez, Daniel (McFarland, 1993)
Abstract or erotic, new Chinese cinema or zombie films, 775 genres are included in this comprehensive reference work. Each entry includes a brief description of the category, the subgenres or related types of films, and a list of movies that best exemplify the genre, showing original title or titles, nationality (73 countries are represented), year of production, additional titles (working title, re-release title, translation, etc.) and director or filmmaker.
Keywords: Cine - Arte Cinematográfico